In Vitro Evaluation of Anticancer Drugs as Antimicrobial Agent against the Pathogenic Enteric Bacteria - Gupta, Pranjali; Gautam, Pankaj; Rai, Nishant (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*309.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962051);" role="presentation">Drug repu<span dir="ltr" style="left: calc(var(--scale-factor)*114.62px); top: calc(var(--scale-factor)*309.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958879);" role="presentation">rposing and drug combination have <span dir="ltr" style="left: calc(var(--scale-factor)*268.49px); top: calc(var(--scale-factor)*309.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956482);" role="presentation">been suggested as a major strategy to counter the spread of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935117);" role="presentation">antimicrobial resistance in clinical and community settings. Drug repurposing explores the potential of existing <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91685);" role="presentation">drugs for new indications with respect to human disease. <span dir="ltr" style="left: calc(var(--scale-factor)*304.75px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914168);" role="presentation">Mainstream anticancer dru<span dir="ltr" style="left: calc(var(--scale-factor)*412.63px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929405);" role="presentation">g paclitaxel and vinblastine <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951068);" role="presentation">were tested as potential efflux pump inhibitors <span dir="ltr" style="left: calc(var(--scale-factor)*267.89px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999855);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*279.17px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02791);" role="presentation">in vitro <span dir="ltr" style="left: calc(var(--scale-factor)*313.03px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.827002);" role="presentation">assays. <span dir="ltr" style="left: calc(var(--scale-factor)*344.59px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941208);" role="presentation">Both the anticancer drugs failed to produce <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948452);" role="presentation">zone of inhibition on MHA plates inoculated <span dir="ltr" style="left: calc(var(--scale-factor)*256.49px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99375);" role="presentation">with <span dir="ltr" style="left: calc(var(--scale-factor)*276.89px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913724);" role="presentation">Salmonella <span dir="ltr" style="left: calc(var(--scale-factor)*324.91px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963139);" role="presentation">Typhi in disk diffusion testing. MIC obtained for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962125);" role="presentation">the two drugs were found as 80μg/ml (Paclitaxel) and 160 μg/ml (vinblastine) respectively. When tested for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93468);" role="presentation">synergy with kanamycin and ciprofloxacin, paclitaxel <span dir="ltr" style="left: calc(var(--scale-factor)*290.21px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91626);" role="presentation">and vinblastine <span dir="ltr" style="left: calc(var(--scale-factor)*353.83px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935921);" role="presentation">resulted in indifference (FIC<span dir="ltr" style="left: calc(var(--scale-factor)*468.34px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938649);" role="presentation">I value <span dir="ltr" style="left: calc(var(--scale-factor)*498.58px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.965842);" role="presentation">=1 for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958415);" role="presentation">both the antibiotics)<span dir="ltr" style="left: calc(var(--scale-factor)*154.94px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956535);" role="presentation">. The combination of anticancer and antibiotic drugs showed bacteriostatic nature in the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907501);" role="presentation">absence of 3log<span dir="ltr" style="left: calc(var(--scale-factor)*135.86px); top: calc(var(--scale-factor)*418.73px); font-size: calc(var(--scale-factor)*6.48px); font-family: sans-serif; transform: scaleX(0.9);" role="presentation">10 <span dir="ltr" style="left: calc(var(--scale-factor)*145.46px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946504);" role="presentation">reduction in viable <span dir="ltr" style="left: calc(var(--scale-factor)*224.69px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913724);" role="presentation">Salmonella <span dir="ltr" style="left: calc(var(--scale-factor)*272.93px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948796);" role="presentation">CFUs over 24 hrs time period in time kill assay. <span dir="ltr" style="left: calc(var(--scale-factor)*473.14px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889311);" role="presentation">Whereas the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94484);" role="presentation">marginal activity was <span dir="ltr" style="left: calc(var(--scale-factor)*161.90px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915565);" role="presentation">observed in EtBr cartwheel assay as compared to control. <span dir="ltr" style="left: calc(var(--scale-factor)*398.35px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901079);" role="presentation">Thus <span dir="ltr" style="left: calc(var(--scale-factor)*421.30px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00754);" role="presentation">in vitro <span dir="ltr" style="left: calc(var(--scale-factor)*453.94px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878916);" role="presentation">studies <span dir="ltr" style="left: calc(var(--scale-factor)*484.66px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93291);" role="presentation">paclitaxel <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912813);" role="presentation">and vinblastine <span dir="ltr" style="left: calc(var(--scale-factor)*135.26px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897079);" role="presentation">cannot be repurposed as antimicrobial against <span dir="ltr" style="left: calc(var(--scale-factor)*320.83px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913724);" role="presentation">Salmonella <span dir="ltr" style="left: calc(var(--scale-factor)*368.35px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.987753);" role="presentation">Typhi.